The stelliferous fold : toward a virtual law of literature's self-formation - Gasché, Rodolphe (Fordham University Press, 2011)
Developing a new approach to literature this text offers a reasssessment of the specificity of literature in distinction from one of its others, namely philosophy, & also takes critical issue with the venerable concept of the text & its association with the artisanal technique of weaving & interlacing.